Conservation and divergence of expression of GA2-oxidase homeologs in apple (Malus x domestica Borkh.) - Zhang, Songwen; Gottschalk, Christopher; van Nocker, Steve (Frontiers in Plant Science, 2023)
In domesticated apple (Malus x domestica Borkh.) and other woody perennials, floral initiation can be repressed by gibberellins (GAs). The associated mechanism is a major unanswered question in plant physiology, and understanding organismal aspects of GA signaling in apple has important commercial applications. In plants, the major mechanism for elimination of GAs and resetting of GA signaling is through catabolism by GA2-oxidases (GA2ox). We found that the GA2ox gene family in apple comprises 16 genes representing eight, clearly defined homeologous pairs, which were named as MdGA2ox1A/1B to MdGA2ox8A/8B. Expression of the genes was analyzed in the various structures of the spur, where flowers are initiated, as well as in various structures of seedlings over one diurnal cycle and in response to water-deficit and salt stress. Among the results, we found that MdGA2ox2A/2B dominated expression in the shoot apex and were strongly upregulated in the apex after treatment with exogenous GA3, suggesting potential involvement in repression of flowering. Several MdGA2ox genes also showed preferential expression in the leaf petiole, fruit pedicel, and the seed coat of developing seeds, potentially representing mechanisms to limit diffusion of GAs across these structures. In all contexts studied, we documented both concerted and distinct expression of individual homeologs. This work introduces an accessible woody plant model for studies of GA signaling, GA2ox gene regulation, and conservation/divergence of expression of homeologous genes, and should find application in development of new cultivars of apple and other tree fruits.